Spurious hypertriglyceridaemia in unconscious patient - Saha, Biswajit (International Journal of Research in Medical Sciences, 2017)
Background: Routine biochemical investigation of one patient admitted with a diagnosis of CVA as mentioned in the requisition revealed high hypertriglyceridaemia in a non-lipemic serum for the first time. Later, after scrutiny of the case sheet in the ward, it was found that apart from other management, blood was drawn about 90 minutes after administration of 4th dose of oral glycerol through nasogastric tube and sent to the laboratory. This was suspected to be the probable cause. In order to find out the degree of interference in blood sample, a small amount of glycerol was brought from the ward to experiment. Methods: Glycerol was initially diluted to 1 in 100 in distilled water and then artificially mixed in various dilutions with pooled serum from indoor patients and pooled heparinized plasma from outdoor patients. These samples were subjected to triglycerides estimation while routine analyses were going on. Results: A concentration of about 13,50,500 mg/dl falsely measured triglycerides was found in glycerol solution. This needed a dilution of 1 in 1500 for distilled water, serum and plasma which had 0, 190 and 113 mg/dl triglycerides respectively to bring the level to near the highest range of linearity. The recovery of added glycerol in distilled water was almost 100% but there was some positive bias more with plasma than serum. Conclusions: The spurious hypertriglyceridaemia in serum resulted from positive interference due to temporary high glycerolaemia by the commonly employed GPO-PAP method for its measurement and would cause the same depending on glycerol level.